Uncovering the impact of social media disseminated misinformation on public health: a study of the effects of false and misleading information on social media on consumer health behaviours and decision making - Ms. Nishtha Sachdev; Dr Rubaid Ashfaq (Journal Healthcare Treatment Development, 2023)
Background: Human beings are inquisitive creatures who are always looking for new information everywhere they go, and from everyone they meet. In the current tech savvy scenario, we seek information from various Social Media platforms. There is significant proclivity in the way information reaches the audience the speed at which it reaches the audience. Social media is a very powerful medium of spreading any kind of information, but not all information is right and useful for the audience. Sometimes the information shared on social media can be misleading and have negative impacts on the course of life of the audience which is consuming it. In adverse situations the information available on public health can either be a boon or curse for the audience. Objective: The objective of this study is to understand the impact social media disseminated misinformation has on the decision making of people, further uncovering the impact it has on their health. Results: The data will be collected by conducting a survey with the audience that spends a significant amount of their day on social media platforms. Data will also be collected by reading various papers on misinformation regarding public health. Conclusions: The study will aid in understanding if the impact of misinformation on public health is positive or negative and in which proportion.